2020
DOI: 10.1039/c9np00016j
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances of metabolic engineering strategies in natural isoprenoid production using cell factories

Abstract: This review covers the strategies mostly developed in the last three years for microbial production of isoprenoid, classified according to the engineering targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
84
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 142 publications
0
84
1
Order By: Relevance
“…3). More generally, the MVA pathway is germane to Archaea and present in most eukaryotes, fungi (Saccharomyces cerevisiae), plant cytoplasm, and some bacteria (enterococci, staphylococci, and streptococci); while the MEP pathway is germane to Bacteria and exists in most cyanobacteria, algae, plant chloroplasts, and some protozoa [147][148][149]. Studies revealed that formation of diverse terpenes, including triterpenes (steroids), brassinosteroids, ubiquinones and most sesquiterpenes originates from the MVA pathway, whereas isoprene, hemiterpenes, monoterpenoids, some sesquiterpenes, diterpenoids, tetraterpenoids, abscisic acid, strigolactones, gibberellins, prenylquinones, and the phytol tail of chlorophylls are derived from the MEP pathway [140,150,151].…”
Section: Isoprenoids Biosynthetic Pathwaysmentioning
confidence: 99%
“…3). More generally, the MVA pathway is germane to Archaea and present in most eukaryotes, fungi (Saccharomyces cerevisiae), plant cytoplasm, and some bacteria (enterococci, staphylococci, and streptococci); while the MEP pathway is germane to Bacteria and exists in most cyanobacteria, algae, plant chloroplasts, and some protozoa [147][148][149]. Studies revealed that formation of diverse terpenes, including triterpenes (steroids), brassinosteroids, ubiquinones and most sesquiterpenes originates from the MVA pathway, whereas isoprene, hemiterpenes, monoterpenoids, some sesquiterpenes, diterpenoids, tetraterpenoids, abscisic acid, strigolactones, gibberellins, prenylquinones, and the phytol tail of chlorophylls are derived from the MEP pathway [140,150,151].…”
Section: Isoprenoids Biosynthetic Pathwaysmentioning
confidence: 99%
“…Among the comprehensive manipulations of microbial metabolism by heterogeneous pathways, two strategies have been used to improve the productivity of microbial cell factories. One strategy focuses on the improvement of biosynthesis by key enzyme activity analysis, evolution and modification, [ 5,6 ] pathway construction and optimization, [ 7 ] and metabolic adaptation of the host strain. [ 8 ] The other strategy focuses on the molecular transfer of intermediates and final products from membrane‐enveloped reaction pools.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to those successful approaches, mining and exploiting key metabolic enzymes with high catalytic efficiencies could be an efficient strategy [28,29]. Metabolic flux towards lycopene production could be effectively improved with the use of substitutive key enzymes with higher catalytic activities along with overexpression strategies [7,25,30].…”
Section: Introductionmentioning
confidence: 99%